Soviet Philosophy and Expertise: One Episode from Volodymyr Shynkaruk - Skrypnyk, Kateryna (Sententiae, 2024)
The first annotated publication of Volodymyr Shynkarukʼs expert opinion (prepared in 1984) on the script for the film “Five Spoons of Elixirˮ by the Strugatsky brothers.